Penyembuhan Jiwa Dalam Perspektif Ibn Hazm: Model Alternatif Bagi Kesehatan Mental - Nafia, Moh Fahmi Ilman; Soleh, Achmad Khudori; Murman, Nawal Aulia (Spiritualita, 2025)
Mental health is a basic aspect of human life that demands an integrative approach. Ibn Hazm Al-Andalusi (994-1064 CE) offered a concept of the soul that combines the rational, emotional, and spiritual dimensions, which is still quite relevant to address contemporary mental health challenges. This study aims to explore Ibn Hazm's thoughts on the concept of the soul, mental illness, and its healing methods, and analyze their relevance in the context of modern psychology. Using qualitative methods with content analysis. The results in this study are (1) the soul as an eternal entity that is the center of morality and human consciousness, which consists of rational and affective aspects. (2) the main root of mental illness consists of three things-psychological problems (such as envy and pride), excessive love of the world, and despair (3) To overcome this, Ibn Hazm compiled an integrated method of healing the soul through self-introspection, correct knowledge, moral training, simplicity of life, and the power of love. This shows that Ibn Hazm's approach is able to enrich contemporary psychological interventions, especially in aspects of spirituality and moral balance. In addition, Ibn Hazm's thought offers an important contribution to the development of Islamic psychology based on cultural and religious values. This research is expected to serve as a foundation for further studies on the integration of classical Islamic concepts with modern mental health practices.